Joint multiuser detection and cancelation of nonlinear distortion effects for the uplink of MC-CDMA systems - Silva, Paulo (2013)
In this paper we consider the uplink transmission in MC-CDMA systems (multicarrier coded division multiple access). To reduce the envelope fluctuations of the transmitted signals, the MC-CDMA signal associated to each MT (mobile terminal) is submitted to a clipping device, followed by a frequency-domain filtering operation. We define an iterative receiver that jointly performs the MUD (multiuser detection) and the estimation and cancellation of the nonlinear distortion effects that are inherent to the transmitted signals. Our performance results show that the proposed receiver structures allow good performances, even for severely time-dispersive channels and/or when a low-PMEPR is intended for each MT.